The dietary supplement Rhodiola crenulata extract alleviates dextran sulfate sodium-induced colitis in mice through anti-inflammation, mediating gut barrier integrity and reshaping the gut microbiome. Issue 7 (17th March 2021) - Wang, Yi; Tao, Hongxun; Huang, Huimin; Xiao, Yaqin; Wu, Xiaoxiao; Li, Mingxing; Shen, Jing; Xiao, Zhangang; Zhao, Yueshui; Du, Fukan; Ji, Huijiao; Chen, Yu; et al.
Abstract : Rhodiola crenulata extract alleviates DSS-induced colitis in mice through anti-inflammation, mediating gut barrier integrity and reshaping the gut microbiome. Abstract : Rhodiola species are edible medicinal plants, which have been traditionally used in both Asia and Europe as an adaptogen, a tonic, an anti-depressant and anti-inflammatory supplement. However, whether it presents a therapeutic effect on colitis or not remains unknown. The aim of this study is to investigate the protective effect of a Rhodiola crenulata extract (RCE) on mice with DSS-induced colitis. RCE significantly alleviated the pathological abnormalities in colitic mice, including the correspondingly increased colon length, ameliorated colonic injury and reduced pro-inflammatory factors. The protective effect was similar to that of the positive control, 5-aminosalicylic acid. The DSS-induced epithelial apoptosis and maintained intestinal barrier function were attenuated by RCE through the upregulation of the level of tight junction proteins such as ZO-1 and occludin. Notably, RCE prevented gut dysbiosis in colitic mice by restoring the microbial richness and diversity, and decreasing the abundance of Proteobacteria phylum and opportunistic pathogenic Parasutterella and Staphylococcus, as well as increasing the abundance of beneficial microbes in Lactobacillus and Bifidobacterium, which were closely correlated with its protective effect against colitis. Meanwhile, chemical characterization of RCE was performed by UPLC-HR-MS to explain its material basis. A total of 63 compounds were identified, while the content of two bioactive ingredients (salidroside, 1.81%; rosavin, 0.034%) was determined.